Service experience co-creation: conceptualization, implications, and future research directions. Issue 2 (20th April 2015) - Jaakkola, Elina; Helkkula, Anu; Aarikka-Stenroos, Leena
Abstract : Purpose: – The collective, interactive aspects of service experience are increasingly evident in contemporary research and practice, but no integrative analysis of this phenomenon has been conducted until now. The purpose of this paper is to conceptualize service experience co-creation and examines its implications for research and practice. Design/methodology/approach: – To map the multi-approach research area of service experience co-creation, the study draws on literature in the fields of service management, service-dominant logic and service logic, consumer culture theory, and service innovation and design, together with invited commentaries by prominent scholars. Findings: – A conceptualization is developed for "service experience co-creation, " and multiple dimensions of the concept are identified. It is postulated that service experience co-creation has wider marketing implications, in terms of understanding experiential value creation and foundational sociality in contemporary markets, as well as in the renewal of marketing methods and measures. Research limitations/implications: – The authors call for cross-field research on service experience, extending current contextual and methodological reach. Researchers are urged to study the implications of increasing social interaction for service experience co-creation, and to assist managers in coping with and leveraging the phenomenon. Practical implications: – For practitioners, this analysis demonstrates the complexity of service experience co-creation and provides insights on the aspects they should monitor and facilitate. Originality/value: – As the first integrative analysis and conceptualization of service experience co-creation, this paper advances current understanding on the topic, argues for its wider relevance, and paves the way for its future development.